Effects of different foxtail millet additional amounts on the cognitive ability of mice. (February 2023) - Fu, Yongxia; Chen, Borui; Liu, Zhenyu; Wang, Han; Zhang, Fan; Zhao, Qingyu; Zhu, Yiqing; Xue, Yong; Shen, Qun
Abstract: Excessive intake of foxtail millet may negatively affect health status due to its low protein digestibility and the presence of anti-nutritional factors. And early-life nutrition supplementation dramatically influences health status. This study aims to investigate the impact of different foxtail millet addition amounts in early life, including 30%, 50%, and 70%, on the cognitive ability of mice to clarify their effects on the health of mice partially . Both 50% and 70% foxtail millet diets caused the cognitive impairment in mice. In addition, foxtail millet interventions caused significant changes in gut microbiota of mice. In particular, mice in the 70% foxtail millet diet group exhibited the most evident changes in gut microbiota and fecal metabolic profile. The bacteria Ileibacterium, unclassified_f__Erysipelotrichaceae, Bifidobacterium, Staphylococcus, and Blautia marked the changes in intestinal flora of mice with the increase of foxtail millet addtion amounts. In addition, tryptophan metabolism and arginine and proline metabolism were the two pathways that contributed the most to the metabolic profile changes due to 50% and 70% foxtail millet diets. Collectively, the cognitive impairment in mice due to 50% and 70% foxtail millet intake was associated with gut microbiota alterations. Highlights: The mice fed with 50% and 70% foxtail millet feeds in early life showed cognitive impairment. Gut microbiota composition and fecal metabolic profile were altered more and more evidently with the foxtail millet addition increasing from 30% to 70%. The changes in the gut microbiota and fecal metabolomics were closely related to the cognitive impairment in the mice fed with 50% and 70% foxtail millet feeds.